2017
DOI: 10.3892/etm.2017.5062
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 downregulation inhibits non‑small cell lung cancer progression in human cell lines

Abstract: Abstract. Mucin 1 (MUC1) is a transmembrane glycoprotein that is aberrantly unregulated in numerous types of cancer, including non-small cell lung cancer (NSCLC), and serves a key role as an oncogene in the tumorigenesis of various human adenocarcinomas. Studies have indicated that MUC1 is involved in cell proliferation, invasion and migration. However, the role of MUC1 in NSCLC progression remains poorly understood. The aim of the present study was to investigate the role of MUC1 in stable MUC1-low-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Similar to our study, a previous study has found that silencing of MUC1 is able to inhibit cell proliferation though the activation of apoptosis pathways and the induction of apoptosis in PANC-1 cells [39]. Additionally, another study has indicated that silencing of MUC1 is capable of inhibiting the development of non-small cell lung cancer cells [17]. As for the role of MUC1 in OSCC, it could be explained by the following reasons.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to our study, a previous study has found that silencing of MUC1 is able to inhibit cell proliferation though the activation of apoptosis pathways and the induction of apoptosis in PANC-1 cells [39]. Additionally, another study has indicated that silencing of MUC1 is capable of inhibiting the development of non-small cell lung cancer cells [17]. As for the role of MUC1 in OSCC, it could be explained by the following reasons.…”
Section: Discussionsupporting
confidence: 86%
“…MUC1 possesses a core protein mass of 120–225 kDa, which increases to 250–500 kDa with glycosylation [14–16]. MUC1 consists of two subunits, namely an N-terminal extracellular subunit (MUC1-N) together with a C-terminal transmembrane subunit (MUC1-C) [17]. It is reported that overexpression of MUC1 is able to induce anchorage independent growth and tumorigenicity [18].…”
Section: Introductionmentioning
confidence: 99%
“…MUC1 is a transmembrane glycoprotein that is aberrantly glycosylated in many cancers, including NSCLC. 253,254 MUC1 and PSCA CAR-T cells showed independent and synergistic antitumor efficacy in a patient-derived xenograft model of NSCLC. 255 The First People's Hospital in Hefei, China is completing a Phase I/ II study of MUC1-CAR T cells for patients with MUC1+ advanced refractory NSCLC (NCT02587689).…”
Section: Ctla-4 Antibodymentioning
confidence: 94%
“…VEGF promotes angiogenesis, regulates the apoptosis of vascular endothelial cells and alveolar epithelial cells and increases the permeability of blood vessels, which leads to sustained tumor growth. For example, Xu [ 33 ] studied the inhibitory effect of MUC1 on NSCLC cells and the results of western blotting indicated that MUC1 significantly reduced the levels of VEGF and VEGF-C proteins, indicating that MUC1 has an anti-angiogenic effect and can be used as a potential treatment for NSCLC. In the present study, the expression level of VEGF decreased significantly when the PAP concentration increased, indicating that PAP could inhibit tumor angiogenesis and inhibit tumor growth.…”
Section: Resultsmentioning
confidence: 99%